2008
DOI: 10.1007/s11832-008-0078-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonunion of fractures of the femoral neck in children

Abstract: The authors present the prospective clinical outcome of nine pseudoarthroses resulting from surgical treatment carried out in nine children, whose ages varied from 6 years and 2 months to 14 years and 2 months (mean 10 years and 2 months), who had fractures of the femoral neck. Five were classified as type II, according to the Delbet classification modified by Colonna, and four were type III. The initial fractures were caused by highenergy traumas, such as trampling, bicycle falls, and car accidents. Treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
(39 reference statements)
0
12
0
7
Order By: Relevance
“…Fracture fixation techniques with low maintainability such as immobilization with a plaster cast, Kirsher wires or fixation with threaded pins are considered to be important risk factors for nonunion. (23,24) In different studies, the incidence of coxa vara after PFNFs has been reported in the range of 7-32%. (14,16,25) The incidence of coxa vara in our cases (16.7%) is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Fracture fixation techniques with low maintainability such as immobilization with a plaster cast, Kirsher wires or fixation with threaded pins are considered to be important risk factors for nonunion. (23,24) In different studies, the incidence of coxa vara after PFNFs has been reported in the range of 7-32%. (14,16,25) The incidence of coxa vara in our cases (16.7%) is consistent with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, complications (e.g., multiple drills, increased fluoroscopy time, uneven screw distribution, head perforation, and failure of internal fixation) may occur during the operation. [35,10,1214] Accordingly, appropriate placement of guide needles is vital to treat FNF with PCS. [17] The use of a SVMN technique was explored to assist in a PCS insertion.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of nine cases done by Pedro et al, they have achieved 100% union rate of their cases done by intertrochanteric valgus osteotomy and plate fixation; they reported only one case of delayed union but it eventually healed. 5 In our case, we have used a K-wire and two non-cannulated cancellous screws. Non-cannulated screws were intentionally used because they are economical and probably exert more compression at the fracture site than a cannulated one.…”
Section: Discussionmentioning
confidence: 99%